A Study on the Standards for Depicting Heliport Charts in Aeronautical Information Services Based on PR Number 6 of 2023 MOS 175-01 Aeronautical Chart: - - Binda Husnun Hanifah Agisya; Dwi Lestary; Surya Tri Saputra (FTK UNSURYA, 2025)
Heliports play a vital role in supporting urban mobility and emergency medical services, necessitating accurate and standardized aeronautical information to maintain aviation safety. The heliport chart, as a specialized type of aeronautical chart, serves as the primary medium for disseminating this information. However, current official charts in Indonesia display significant inconsistencies and missing data, potentially leading to misinterpretation by pilots. This study assesses the adequacy of existing internal standards for heliport chart production and their alignment with the Ministry of Transportation Regulation (PR) No. 6 of 2023, which governs the depiction of aeronautical charts under MOS 175-01. A qualitative approach was employed, including comparative analysis of published heliport charts, direct observation, and semi-structured interviews with cartographic personnel at AIS units in Jakarta and Denpasar. The results reveal that the current standard operating procedures (SOPs) are overly generic, lack specific provisions for heliport facilities, and fail to fulfill regulatory requirements. These deficiencies result in inconsistent chart content, omission of critical operational information, and reduced production efficiency. To address these issues, it is recommended to develop a distinct and detailed standard dedicated to heliport chart production in compliance with PR 6 of 2023. Such standardization is crucial to ensure clarity, completeness, and consistency of heliport charts, ultimately enhancing both flight safety and cartographic workflow effectiveness.